Confinement of Ru nanoparticles inside the carbon nanotube: Selectivity controls on methanol decomposition - Park, Se-Won; Park, Ji Hoon; Yoon, Chang Won; Lee, Jin Hee (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2020)
Carbon nanotubes (CNT) have been widely used as catalyst supports, and the confinement of metal nanoparticles inside the CNT cavity have received much attention. In this study, graphitic carbon nitride were used to introduce nitrogen to CNT and form ruthenium nanoparticles inside the CNT channel. The XPS evidenced that the ruthenium nanoparticles in the CNT cavity are present in more reduced state, and the nitrogen species are in a pyridinic and a pyrrolic form. The prepared catalysts exhibited excellent hydrogen and carbon monoxide selectivity. The hydrogen-to-carbon monoxide ratio was close to the stoichiometric ratio of methanol decomposition. In contrast, the ruthenium nanoparticles outside the CNT showed lower carbon monoxide selectivity at high methanol conversion. The alteration of electrical properties of ruthenium nanoparticles by the CNT channel and N-doping might hamper side reactions, such as water gas shift, methanation, dimethyl ether formation upon methanol decomposition.
Keywords: FACILE SYNTHESIS; RUTHENIUM; CATALYSTS; NANOCATALYST; OXIDATION; DIOXIDE; SITES; OXIDE; GAS